Communions communistes (1966-1972)Une iconographie politique de l’eucharistie - Aurel Rotival (Mise au Point)
This article suggests to study an aesthetic pattern shared by three European movies, directed between the ‘60s and the ‘70s. The Hawks and the Sparrows (P. P. Pasolini, 1966), Long Live Death (F. Arrabal, 1971), and Red Psalm (M. Jancsó, 1972), are all three characterized by a sequence that replay politically the religious scheme of communion, directly borrowed from the Christian sacrament of the Eucharist. It is about seeing in this figurative community the index of a singularly apocalyptic moment experienced by the Western world. Following this catastrophic diagnosis, it is with the religious notion of salvation that a certain section of European Marxism had to think the political concepts of revolution and emancipation. This should lead some communist artists and thinkers to reconsider afresh the memorial, communal and salvific virtues originally transported by religious representations and ceremonies – a turning point, both anthropological and religious, whose communist communions spotted in these three films bear the mark. These three examples are also an opportunity to pay attention to the contextual conditions which, in European cinema, can encourage the emergence of common themes and patterns transcending generic, stylistic or regional differences.